2008
DOI: 10.2472/jsms.57.8
|View full text |Cite
|
Sign up to set email alerts
|

Study on Crack Propagation Velocity of Mortar/Granite Specimens by Impact Test

Abstract: In this study, the static and impact splitting tensile tests were carried out by loading the cylindrical mortar/granite specimens horizontally, and the crack propagation velocities were obtained by the image analysis using the ultra high-speed video camera, which is the fastest in the world, developed by Etoh et al.(2003). The correlations between the impulse and the crack propagation velocity indicate that there appears to be a critical state in which the crack propagation velocity does not exceed a certain v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…They have also shown that the shockfailure behavior of a mortar specimen significantly changes with the magnitude of the impulse. Recently, Tamano et al [3] visualized the shock crack propagation in a mortar specimen by using the above-mentioned high-speed video camera. Their results indicate that the crack propagation velocity increases as the impulse force increases at relatively low impulse, but the crack propagation velocity reaches an upper bound value with the large impulse.…”
Section: Introductionmentioning
confidence: 99%
“…They have also shown that the shockfailure behavior of a mortar specimen significantly changes with the magnitude of the impulse. Recently, Tamano et al [3] visualized the shock crack propagation in a mortar specimen by using the above-mentioned high-speed video camera. Their results indicate that the crack propagation velocity increases as the impulse force increases at relatively low impulse, but the crack propagation velocity reaches an upper bound value with the large impulse.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering methods to perceive the mechanical state of stone bridges include configuration measurements and strain measurements (Tamano et al, 2009). As for the safety management of arch-type stone bridges by deformation measurements, there is a limit to perceiving the distinct mechanical tendencies, because the deformation is extremely small.…”
Section: Strain Measurementsmentioning
confidence: 99%